Odpowiedź :
1] [tex]x^2+8x+16=(x+4)^2[/tex]
2] [tex]4x^2-4x+1=4[x^2-x+0,25]=4(x-0,5)^2[/tex]
3] [tex](5-\sqrt{7})\cdot(5+\sqrt{7})=5^2-(\sqrt{7})^2 =25-7=18[/tex]
4] [tex](\sqrt{7}+1)^2=(\sqrt{7})^2+1^2+2\cdot\sqrt{7}\cdot1=7+1+2\sqrt{7}=8+2\sqrt{7}=2(4+\sqrt{7})[/tex]
Szczegółowe wyjaśnienie:
[tex]x^2+8x+16=\underbrace{x^2+2\cdot x\cdot4+4^2}_{(a+b)^2=a^2+2ab+b^2}=(x+4)^2\\\\\\4x^2-4x+1=\underbrace{(2x)^2-2\cdot2x\cdot1+1^2}_{(a-b)^2=a^2-2ab+b^2}=(2x-1)^2\\\\\\\underbrace{(5-\sqrt7)(5+\sqrt7)}_{a^2-b^2=(a-b)(a+b)}=5^2-(\sqrt7)^2=25-7=18\\\\\\(\sqrt7+1)^2=\underbrace{(\sqrt7)^2+2\cdot\sqrt7\cdot1+1^2}_{(a+b)^2=a^2+2ab+b^2}=7+2\sqrt7+1=8+2\sqrt7[/tex]